To give place(-s) to the event. A critical reception of Renaud Barbaras’ phenomenological cosmology - Llorente Cardo, Jaime (Revista de Filosofía, 2026)
This study undertakes a critical examination of the terms in which Renaud Barbaras formulates his recent “phenomenological cosmology,” organized around the concept of an originary “deflagration.” The inquiry aims to bring to light both the unspoken presuppositions and the latent implications that follow from the adoption of “belonging” as the epistemological correlate of ontological deflagration within a horizon still marked by the inherited bifurcation between subjectivity and worldhood. In its final movement, the analysis seeks to show in what sense this phenomenological cosmology may be understood as a covert attempt to reconcile “man” and “world”: a gesture oriented toward securing for the former a fully inhabited status at the heart of the latter, that is, an authentic mode of “dwelling” in a sense resonant with Heidegger’s own conception.